Priming and cryopreservation of microencapsulated marrow stromal cells as a strategy for intervertebral disc regeneration. (14th March 2018) - Naqvi, Syeda M; Gansau, Jennifer; Buckley, Conor T
Abstract: A challenge in using stromal cells for intervertebral disc (IVD) regeneration is their limited differentiation capacity in vivo without exogenous growth factor (GF) supplementation. Priming of stromal cells prior to transplantation may offer a feasible strategy to overcome this limitation. Furthermore, the ability to cryopreserve cells could help alleviate logistical issues associated with storage and transport. With these critical translational challenges in mind, we aimed to develop a strategy involving priming and subsequent cryopreservation of microencapsulated bone marrow stromal cells (BMSCs). In phase one, we utilised the electrohydrodynamic atomisation process to fabricate BMSC-encapsulated microcapsules that were primed with TGF-β3 for 14 d after which they were cultured for a further 21 d under basal or GF supplemented media conditions. Results showed that priming induced differentiation of BMSC microcapsules such that they synthesised significant amounts of sGAG (61.9 ± 2.0 μ g and 55.3 ± 6.1 μ g for low and high cell densities) and collagen (24.4 ± 1.9 μ g and 55.3 ± 4.6 μ g for low and high cell densities) in continued culture without GF supplementation compared to Unprimed microcapsules. Phase two of this work assessed the extracellular matrix forming capacity of Primed BMSC microcapsules over 21 d after cryopreservation. Notably, primed and cryopreserved BMSCs successfully retained the ability to synthesise both sGAG (24.8 ± 2.7 μ g and 75.1 ± 11.6 μ g for low and high cell densities) and collagen (26.4 ± 7.8 μ g and 93.1 ± 10.2 μ g for low and high cell densities) post-cryopreservation. These findings demonstrate the significant potential of priming and cryopreservation approaches for IVD repair and could possibly open new horizons for pre-designed, 'off-the-shelf' injectable therapeutics.